The doctrinal differences of Calvinism and Arminianism - Nascimento, Jeverson (Vox Scripturae - Revista Teológica Internacional, 2018)
The present article has the objective of presenting reflections on the doctrinal differences Calvinism (defended by Calvinism), and Arminian (from the point of view of Arminianism), conceptualizing them, addressing the main doctrines that support these theological lines, their divergences, their main followers and reflections on them. Calvinism bears this name because of its forerunner John Calvin, and its main doctrines are Total Depravity, Unconditional Election, Limited Atonement, Irresistible Grace and Perseverance of the Saints. Already Arminianism was the name given to the theological and doctrinal line coming from the followers of Jacob Arminius, whose main doctrines are: Free Will, Conditional Predestination, Universal Atonement, Grace can be prevented and Decay of Grace. The divergences between these two lines theological doctrines circulate between these main doctrines presented and in the conceptualization of each of them. It is concluded that both Calvinism and Arminianism constitute two theological systems that attempt to explain the relationship between God’s sovereignty and human responsibility for salvation and that both are based on biblical texts, a fact that has generated divergences since 1610 and still reflects in the Christian life of society.
Keywords: Doctrinal differences; Calvinism; Arminianism